2021
DOI: 10.1007/s11356-020-12130-y
|View full text |Cite
|
Sign up to set email alerts
|

The influence of technological innovation and human capital on environmental efficiency among different regions in Asia-Pacific

Abstract: This study employs super-efficiency DEA model with desirable inputs and an undesirable output in calculating environmental efficiency values in different regions in Asia-Pacific from 1990 to 2018. The study compares environmental efficiency index in South East Asia, South Asia and East Asia. The study also evaluates the determinants of environmental efficiency using truncated regression. The mean environmental efficiency score demonstrates that East Asia region is highly efficient whereas South East Asia is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 62 publications
3
22
0
1
Order By: Relevance
“…Renewable energy is the key to limiting greenhouse gas emissions and limiting the increase in global temperature by 2 • [156]. The continents were also investigated: Asia was studied in [157][158][159], and the African continent in [160]. The most localized studies have a concentration on research focused on China [161][162][163].…”
Section: Discussionmentioning
confidence: 99%
“…Renewable energy is the key to limiting greenhouse gas emissions and limiting the increase in global temperature by 2 • [156]. The continents were also investigated: Asia was studied in [157][158][159], and the African continent in [160]. The most localized studies have a concentration on research focused on China [161][162][163].…”
Section: Discussionmentioning
confidence: 99%
“…However, after income get to a certain threshold, ecological efficiency improves with further enhancement in income per capita thus, this nexus exhibits a U-shaped curve. Several studies support this hypothesis [11,55]. Moreover, Moutinho et al [56] investigated the effect of income on efficiency using the super-SBM approach and reported that PGDP has a negative impact on environmental efficiency in Germany.…”
Section: Index Selection Of Contextual Variablesmentioning
confidence: 98%
“…To test the nexus between growth and DSTFEE in Africa, the study presents the following nonlinear model by following prior such [11,54].…”
Section: Regression Technique Via Bootstrap Truncation Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Fukuyama et al (2020) measured Japan's environmental efficiency by the two-stage network production model in their research and studied the relationship between environmental and energy efficiency and Japanese happiness [12]. Twum et al (2021) measured the environmental efficiency values of different regions in the Asia-Pacific region from 1990 to 2018 by super-efficiency DEA model and proved the inverted U-shaped link between environmental efficiency and technological innovation [13]. conducted a study on China's regional industries from 2011 to 2015, regarding SO 2 and solid waste emissions as undesirable output [14].…”
Section: Literature Reviewmentioning
confidence: 99%